Development of imitation model for selection of tug barge vessels for work on the line - Shcherbina, Olga (Technology audit and production reserves, 2017)
The object of research is the process of operation of TBV for route transport with a through form of traction and exchangeable form of coordination of the work of traction and tonnage at the points of departure and destination. One of the most problematic places is the lack of research in the scientific literature studied of solved the task of forming a number of priority vessels for the subsequent organization of their work in designated organizational form. The imitation model proposed in the study makes it possible to perform a preliminary selection of vessels for work on traffic schema, which simplifies the calculations associated with the distribution of vessels. The model is based on the need to take into account the physical and geographical factors in the organization of the work of the TBV on inland waterways in order to ensure the greatest correspondence of the linear and technical characteristics of the ships to the conditions of the forthcoming voyage. The developed group of limitation takes into account the characteristic of the considered form of the organization of TBV and is rational only for it, since it takes into account that the TBV immersed in the port of departure should go to the destination without re-forming and loading (unloading). Thanks to the proposed methodology, it is planned to increase the profit of the shipping company by increasing the carrying capacity of the vessel with the best alignment of the transport characteristics of the TBV and the route.